Pelatihan e-Learning bagi Para Guru SMAIT Al-Ukhuwah Pagaden Subang Jawa Barat Berbasis Edmodo - Nur Cholis; Damora Rhakasywi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
One of the learning management system learning is Edmodo. Edmodo was developed based on the principles of group-based classroom management and social media. E-learning is expected to be able to reduce obstacles in the implementation of teaching and learning activities that are no longer limited by distance and time. Teachers and students no longer need to come face to face and interact through the e-learning application. Edmodo learning media is used by students, teachers and parents to monitor their children's learning development. Students who use Edmodo can discuss with each other whenever and wherever subjects with other students related, increase the interaction of lecturers with students, they can be more independent in learning, and material that has been uploaded by lecturers can be downloaded by students and used as a learning reference source. In addition, assignments are given through the assignment and quiz features that have a time limit so that they can train discipline in doing the task. The service team empowered the teachers and students in the teaching and learning process using the e-learning system in the form of Edmodo training at Al-Ukhuwah Subang High School. How to cite:Cholis, N., Rhakasywi, D. (2020). Pelatihan e-Learning bagi Para Guru SMAIT Al-Ukhuwah Pagaden Subang Jawa Barat Berbasis Edmodo. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang,5(1), 79-84.DOI: https://doi.org/10.26905/abdimas.v5i1.3641